Dietary intake, forest foods, and anemia in Southwest Cameroon - Tata, C.Y.; Ickowitz, A.; Powell, B.; Colecraft, E.K. (Public Library of Science, 2019)
Forest cover has been associated with higher dietary diversity and better diet quality in Africa. Anemia prevalence among women of reproductive age in sub-Saharan Africa is very high and diet is one known contributor of a high prevalence rate. We investigated whether living in communities with high forest cover was associated with better diet quality and lower anemia prevalence among women of reproductive age in Southwest Cameroon.